Electron tubes and semiconductors - Defrance, Joseph J (Prentice- Hall, Inc, 1962)
Electron tubes and semiconductors / Defrance, Joseph J. -- Englewood Clifs, N.J: Prentice- Hall, Inc, 1962 621.38151 J84 No. of Copies : 1